In-house rose Bengal plate agglutination test (RBPT) for a rapid diagnosis of Brucellosis in goats in Malaysia - Othman, Shahaza; Bejo, Siti Khairani; Zakaria, Zunita; Bahaman, Abdul Rani (Medwell Journals, 2009)
The Rose Bengal Plate Test (RBPT) antigens from Brucella melitensis local isolates (in-house RBPT) were prepared and compared with RBPT antigen for Brucellosis in sheep and goats prepared by Veterinary Laboratory Agency, UK. Eight hundred fifty-six sera samples, of which were collected from goats were examined with the RBPT and Complement Fixation Test (CFT). The RBPT and CFT results showed that the in-house RBPT antigen was superior to the commercial prepared RBPT antigen (VLA, UK). Out of 856 sera analyzed by in-house RBPT, commercial RBPT and CFT, 30.84, 26.40 and 31.65% were found to be Brucella positive, respectively. The sensitivity calculated for the in-house RBPT compared with CFT was 85.24% whilst that of commercial RBPT was 78.59%. Therefore, it was conclude that in-house RBPT antigens could be prepared and used for epidemiological surveillance of Caprine brucellosis in Malaysia.